Editorial - El Enshasy, Hesham A.; Sarmidi, Mohamed R. (International Journal of Biotechnology for Wellness Industries, 2012)
Editorial - Inaugural issue - Volume 1 Number 1 International Journal of Biotechnolgy for Wellness Industries